Development, religiosity, and women’s formal employment in the MENA region: an exploratory study - Karimi, Donya (Kansas State University, 2020)
The Middle East and North Africa (MENA) have seen significant changes in human development indicators that suggest considerable improvement in people’s lives. As a result of development, the total fertility rate for the region has dropped, and access to secondary education has increased in most nations in the region. However, throughout the region, many development outcomes remain gendered: that is, women and men do not share equally the benefits of development. For example, the women’s labor force participation rate, a key measure of development, is the lowest in the world. The individual and national factors impacting women’s right to employment are not well understood. Thus, this study in examining attitudes toward women’s equal right to employment looks at individual-level indicators as well as relevant economic, political, and cultural factors. First, I reviewed the existing theories and literature related to the status of women in the region and developed a comprehensive theory of the factors that shape attitudes toward women’s right to employment. This study creates a more comprehensive model to understand the factors behind the low rate of women’s labor force participation in the MENA region. This is followed by two sets of analyses that examine the impact of these factors. In the first set of analyses, considering the nested structure of the dataset, the hierarchical linear model (HLM) that takes the hierarchical structure of the data into account is applied to analyze the dataset. The cross-level interaction analysis also is applied to explain variation in individual religiosity using level 2 predictors. The HLM and cross-level outcomes indicate that the cultural, economic, and political differences of the study nations have a significant effect on their support for women’s equal rights in the labor market. Consequently, individual-level predictors of egalitarian gender attitudes may also have different predictive power across the nations. Thus, in the second set of analyses, I compare individual attitudes toward women’s rights to employment within the sixteen MENA nations available in the World Values Survey (WVS) using years 2001, 2007, and 2014 and employing the logistic regression model. Findings show a clear variation among MENA nations regarding the individual and national indicators of gender ideology, which, in turn, results in different statuses for women in each nation. The analysis of this study indicates that nations cannot be unified regarding egalitarian gender ideology and their attitudes toward women’s rights in the labor market. Different factors are associated differently with attitudes toward women among the nations. Thus, the attempt to rank or categorize countries in the MENA region regarding women’s status is possible but complicated and difficult.
Keywords: Development; Middle East and MENA region; Women; Labor force; Religion; Sociology